2018
DOI: 10.1080/02508281.2018.1498158
|View full text |Cite
|
Sign up to set email alerts
|

Familiar tourists, their behaviours and place attachments: an empirical framework

Abstract: Recognising the importance of familiar places in the lives of individuals and its prevalence in society, this paper examines the behaviours of familiar tourists and their relationships with their familiar places. Stimulated by conceptual work by Pearce (2012) alongside personal observation of the phenomenon, and with input from early focus group work, the fieldwork was conducted in two rural and peripheral destinations of Wales in the United Kingdom across peak and shoulder periods. This paper contributes a mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 50 publications
0
8
1
Order By: Relevance
“…These differences contradict what would be expected from second homeowners as a whole given the relationship between place attachment and nostalgia (e.g. Clarke & Bowen, 2018;Tsai, Hsu, & Chen, 2020). Instead, these findings indicate a similar dynamic as has been observed between the place attachment of permanent residents and second homeowners.…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…These differences contradict what would be expected from second homeowners as a whole given the relationship between place attachment and nostalgia (e.g. Clarke & Bowen, 2018;Tsai, Hsu, & Chen, 2020). Instead, these findings indicate a similar dynamic as has been observed between the place attachment of permanent residents and second homeowners.…”
Section: Discussioncontrasting
confidence: 69%
“…Nostalgia has been investigated thoroughly in relation to sports tourism (e.g. Cho et al, 2014;Joseph, 2011;Ramshaw & Gammon, 2005;Wood & Gabie, 2011) as well as other contexts, such as heritage tourism (Lee, 2015), seaside tourism (Jarratt, 2015), dark tourism (Bigley et al, 2010), and place attachment (Clarke & Bowen, 2018;Tsai et al, 2020). Clarke and Bowen (2018) found that tourists may develop "nostalgic bonding (with place)," particularly in relation to early adulthood.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Many scholars discussed the meaning of sustainable tourism; see as samples (Nunkoo, 2017;Fodness, 2017;Bramwell &Lane, 2015 andHall, 2016) (Clarke and Bowen, 2018). Every destination based on its particular characteristics and resources plans some types of tourism.…”
Section: Theoretical Overview Of the Tourismmentioning
confidence: 99%
“…Patterns and systems of tourism vary as time passes. The changes arise from various cultures, environments, climates, and ecosystems of regions [17].…”
Section: Introductionmentioning
confidence: 99%